Robust adaptive tracking control of an underactuated ship with guaranteed transient performance. Issue 2 (25th January 2017) - Gao, Tingting; Huang, Jiangshuai; Zhou, Yong; Song, Yong-Duan
ABSTRACT: In this paper, a robust adaptive controller for a underactuated ship is proposed to make the ship follow a predefined path with guaranteed transient performance and arbitrarily small steady-state position error and orientation error, despite the presence of environmental disturbances induced by wave, wind and ocean current and unknown system parameters. We design a new adaptive state feedback controller and parameter estimators to guarantee converging exponentially by assuming all states are available. It is shown that the mean-square tracking errors are of order of an arbitrarily small design parameter, and the position error and the orientation error also decrease at a pre-specified exponential rate. Simulations with a commercial monohull ship using Matlab also demonstrate the effectiveness of the controllers.